Role of participation in decision making and social capital on sustainability of watershed usage among peri-urban agricultural farmers of Kwadon, Gombe State, Nigeria - Ibrahim, Muhammad Bello (2016)
Participation and social capital is a medium for promoting watershed sustainability among peri-urban agricultural farmers. Previous literature has indicated good relationship between social capital and resource sustainability among rural farmers. However most of the previous studies did not consider level of decision – making to participate in peri-urban agriculture (PUA) and role of social capital in sustainably managing water usage in watersheds which the researcher perceived as limitations in the studies. In efforts to bridge this gap, this study focused on looking at the level of decision-making in participation into PUA and social capital and examined their relationship in promoting sustainability of watershed resources. The study also examined moderating effect of social capital on sustainability of watershed water resources. Based on this, the researcher developed a hypothesized conceptual model of social capital (bonding, bridging and linkage) and their level variation in predicting dimensions of sustainability of watershed water resources. In this quantitative study, a total of 217 respondents were surveyed and a purposive sampling technique was used to select the respondents from the three carefully divided area of the Kwadon watershed. Data was gathered using structured questionnaire in which some parts were adopted from previous literature and the administration of the questionnaire was done by the researcher and trained research assistants. Moderating effect of social capital domain was made with dependent variable: sustainability of watershed usage and analysis indicated that most of the items measured have a positive moderating effect with the exception of land problem issues and government support showing no significant moderation effect on sustainable watershed usage. Based on this result the researcher concluded that, participation in decision-making into PUA coupled with existence of social capital within the farmers helped in contributing significantly to sustainability of watershed usage at moderate level. The findings of this study can be used by government, rural farmers and Non-governmental organizations (NGOs) in developing ways of improving participation and social capital for higher levels of sustainability of watershed usage for peri-urban agriculture (PUA).